PENYEBAB KEGAGALAN DIVERSI DI PENGADILAN NEGERI KOTA BAUBAU - Rizky Amalia, Wa Ode Syahrina; Umar, Firman; Heri, Ririn Nurfaathirany (Jurnal Tomalebbi, 2024)
This research aims to determine the factors causing the failure of diversion at the Baubau City District Court. The research approach used is qualitative research with a qualitative descriptive research type. Data collection techniques include observation, interviews and documentation using research instruments in the form of interview guides, recording and documentation tools. Triangulation and member checking are used as procedures to check the validity of the data, as well as using data reduction, data presentation, and drawing conclusions as data analysis techniques. The research results prove that the factors inhibiting diversion include a) legal substance factors in accordance with article 7 of the SPPA Law b) legal structure factors and law enforcement officers. Diversion failure occurred because the victim wanted to continue the case through legal channels. c) Legal culture or legal culture factors. People think that Butonese people usually have high levels of egoism.